Dynamic behaviour of the track in transitions zones considering the differential settlement. (27th October 2019) - Wang, Haoyu; Markine, Valeri
Abstract: Transition zones in railway tracks are the locations with considerable changes in supporting structures. Because of the difference in the structures or material properties, the differential settlement always present. The structural vibration caused by the hanging sleepers is often observed in transition zones, which leads to significant amplification of dynamic responses between the ballast and sleeper, aggravating the track degradation. In order to explain the high degradation rate of the track in transition zones, a 3D dynamic (explicit) Finite Element model of transition zones has been used. It considers that the rapid compaction of ballast tracks occurs after a few months of operation, while the track on the engineering structure barely settles, resulting in the appearance of hanging sleepers in transition zones. Therefore, the model can study the differential settlement and the stiffness variation between the ballast track and the engineering structure at the same time. Nonlinear contact elements are used to model the interface between sleepers and ballast so that the behaviour of hanging sleepers can be better studied. The results show that the differential settlement plays a more important role in track degradation than the stiffness variation. The dynamic behaviours are different in the embankment-bridge and bridge-embankment transitions. The location that the maximum wheel-rail interaction force appears does not correspond to that of the maximum ballast stress. The results explain the degradation mechanism and provide guidance for maintenance.